If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45 + 4m = 61 + 2m Solving 45 + 4m = 61 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 45 + 4m + -2m = 61 + 2m + -2m Combine like terms: 4m + -2m = 2m 45 + 2m = 61 + 2m + -2m Combine like terms: 2m + -2m = 0 45 + 2m = 61 + 0 45 + 2m = 61 Add '-45' to each side of the equation. 45 + -45 + 2m = 61 + -45 Combine like terms: 45 + -45 = 0 0 + 2m = 61 + -45 2m = 61 + -45 Combine like terms: 61 + -45 = 16 2m = 16 Divide each side by '2'. m = 8 Simplifying m = 8
| 2(4x+5)+(3x+1)= | | -13o-8=-35 | | -a^2-10a-21=0 | | 4(p-1)+5(p+1)=10 | | -(4x+5)-5(x+2)= | | 5x=3.5 | | 4(2x+2)-2(3x-3)= | | 8x^2+16x-1=0 | | x-3.6=0 | | (6x-7)=(4x-23) | | 43=20 | | 5x+2=10+3x | | 8x(n+3)=72 | | n+2=-10+10n-6 | | 3(5k+4)-22k+4+3= | | 3h^2+21h+18=0 | | 4y+50-26=2y | | 3h^2+21+18=0 | | 2x+27=15 | | 3(x-3)-16=2(x-8)+9 | | -5(4x+2)-2(2x+4)= | | 9t^2+9t+2=0 | | 2-2x=3x-33 | | -16x^2+135x+76=0 | | 4(2x-2)+3(2x-3)= | | 10x=2(7x+3) | | 14x+15=7x+50 | | 7(x+4)=7x-56 | | 10y-8=9y-10 | | 6x^3-30x^2+42x-10=0 | | x-1.6=2.4 | | 3m-4+3m-4+m=76 |